Propuesta de un sistema de producción de hidrógeno partiendo de etanol (2020)
This theorical document display a review and explain the most representative methods for hydrogen production from ethanol, where depending on its oxidative agent or energy source are classified in different ways; for that reason, here is presented a decision Pugh matrix to compare the disadvantages and perspectives of the 13 explained methods, selecting among all the ethanol steam reforming. An analysis was made of the state of art of the developed catalyst until the moment for the ethanol steam reforming, focusing on those with Co, Ni and bimetallic active metal, selecting four of them: Co/Sep, Co/CeO2, SiO2-Co0.75Mg0.25O and Ni/10Mg- ATP, which were compared physiochemically, finding that because of it structural properties and good activity, the catalyst SiO2-Co0.75Mg0.25O deserve more investigation, so it is proposed as part of an H2 production system at laboratory scale.